Impact of COVID-19 Outbreak on the Gynecological Outpatients HPV Infection Rate in Wuhan, China: A Retrospective Observational Study - Liu, Hang; Yao, Qian; Li, Di; Zhao, Zhiming; Li, Yan (Frontiers in Medicine, 2022)
Background: The outbreak of SARS-CoV-2 has caused millions of deaths and greatly influenced the timely diagnosis and treatment of other diseases. In addition, the pandemic dramatically reduced the prevalence of several sexually transmitted infections. However, the impact of this pandemic on the HPV infection rate has not been well investigated. Materials and Methods: We retrospectively gathered the HPV and cervical cancer screening data of outpatients in gynecological clinics of a tertiary hospital from December 1, 2018 to December 31, 2020 in Wuhan. Based on the timeline of the SARS-CoV-2 pandemic in Wuhan, we divided this period into four relatively independent stages to compare the HPV screening visit numbers and infection rates. Results: Compared with before the pandemic, during the pandemic, the HPV screening visits and HPV infection rate dropped dramatically by approximately 50% and 10%, respectively. The strict lockdown measures greatly decreased the HPV infection rate (17.03 vs.8.29, P=0.003). During the pandemic, the most prevalent HPV genotypes were HPV 16, 52, 58, and 53. After the pandemic, the HPV infection rate quickly recovered, but it was still slightly lower than the infection rate before the outbreak (23.3% vs. 21.2%). Conclusion: During the COVID-19 pandemic, cervical cancer screening visits and HPV infection rates have decreased dramatically. The HPV transmission has also decreased after the strict lockdown measure. Effective HPV and cervical cancer screening programs should be strengthened immediately to reduce the transmission of HPV during and after the pandemic.